THE EFFECT OF SERVICE QUALITY AND MENU VARIATION ON PURCHASING DECISIONS - Febby Erisca; Tri Utari Ismayuni (Jurnal Ekonomi, 2023)
The middle class restaurant is Ayam Penyet Cindelaras Kualanamu, Deli Serdang, North Sumatra. Loyal customers of Kualanamu's Ayam Penyet Cindelaras in Deli Serdang, North Sumatra, have made it a special place in their hearts. However, the benefits presented by this restaurant are not ideal. Customers continued to voice their dissatisfaction with the various services, as well as the cleanliness, portion sizes, tidiness, and empathy of the employees at the restaurant. This can obviously affect the purchase choice. At Ayam Penyet Cindelaras Kualanamu, Deli Serdang, North Sumatra, the purpose of this study was to find out how consumer purchasing decisions are influenced by service quality and menu variety. Explanatory research is the term for this type of research. The population of this study consisted of 100 respondents who were customers of Ayam Penyet Cindelaras Kualanamu, Deli Serdang, North Sumatra. In this study, accidental and purposeful non-probability sampling was used as the sampling method. Cross tabulation, correlation test, determination, and linear regression are the analytical techniques used.